SPEET: software tools for academic data analysis - Vilanova, Ramon (2018)
The international ERASMUS+ project SPEET (Student Profile for Enhancing Engineering Tutoring) aims at opening a new perspective to university tutoring systems. Before looking for its nature, it’s recommended to have a look on the current use of data in education and on the concept of academic analytics basically defined as the process of evaluating and analysing data received from university systems for reporting and decision making reasons. This work reflects the outputs of the SPEET project in relation to the data mining tools, specific algorithms developed to deal with the basic problems tackled in the project: Classification, Clustering and Drop-out Prediction.